(3GdfcJ hGdYjhf aj GdJaSjQs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s ((3LYaQ Hf Ydj Hf CHj eMeO YHOGdZfj GdeYQha HCHf CHj GdVHjH s)
(3ChdgG (B:s
(3jHJOF HShQI GdaGJMI s
(3BNQgG (B:s
(3hjfJgj HBNQ ShQI GdeGFOg s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1978s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs